Tahlil kitab Syarah Mukhtasharun Zidan Ta'lifu As- Said Ahmad Zaini Dahlan - Syahriana Hasibuan (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2022)
Textbooks are informational materials or educational materials in the form of supporting books for learning the Arabic language. Syarah Mukhtashor Jiddan Ta’lifu As- Said Ahmad Zaini Dahlan is searches for the rules and purpose, and this book has the statement in detail. A very short explanation book that has the characteristics of the soul. It uses easy language (everyday language), simple examples, and complete parsing.The research background of this thesis is one of the success factors in teaching the subject, and the teacher must choose the good material or the book that is good in his teaching. The method used in this research is desk research. The method used is the descriptive analytical method. The tools for collecting information are observation, documentation and information analysis. As for the result obtained from this research, they are materials in a very brief explanation book that is composed of twenty-five chapters, and in it the investigations use the language easy to facilitate the concept of the students, which Ahmad Zaini Dahlan explained